2020
DOI: 10.1021/acs.inorgchem.0c01013
|View full text |Cite
|
Sign up to set email alerts
|

Probing Mg Intercalation in the Tetragonal Tungsten Bronze Framework V4Nb18O55

Abstract: While commercial Li-ion batteries offer the highest energy densities of current rechargeable battery technologies, their energy storage limit has almost been achieved. Therefore, there is considerable interest in Mg batteries, which could offer increased energy densities compared to Li-ion batteries if a high-voltage electrode material, such as a transition metal oxide, can be developed. However, there are currently very few oxide materials which have demonstrated reversible and efficient Mg 2+ insertion and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…28 Electrochemical analysis of the two materials under study was performed in conditions previously found to give high degrees of Mg insertion (110°C in 0.5 Mg(TFSI) 2 in PY 14 TFSI ionic liquid electrolyte). 23,24 For the first discharge/charge cycle of the V 2 O 5 sample, the behavior resembled that observed in bulk α-V 2 O 5 previously by Yoo et al, 23 i.e. a capacity of >200 mA h g −1 with a very large calculated voltage hysteresis of 1.68 V (Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…28 Electrochemical analysis of the two materials under study was performed in conditions previously found to give high degrees of Mg insertion (110°C in 0.5 Mg(TFSI) 2 in PY 14 TFSI ionic liquid electrolyte). 23,24 For the first discharge/charge cycle of the V 2 O 5 sample, the behavior resembled that observed in bulk α-V 2 O 5 previously by Yoo et al, 23 i.e. a capacity of >200 mA h g −1 with a very large calculated voltage hysteresis of 1.68 V (Fig.…”
Section: Resultssupporting
confidence: 82%
“…This irreversibility has been commonly observed in metal oxide electrodes with Mg electrolytes. 23,24 Fig. 4c and d also depicts integrated O K-edge X-ray absorption spectra acquired for pristine and electrochemically cycled V 2 O 5 -TiO 2 samples, compared with standard α-V 2 O 5 .…”
Section: Resultsmentioning
confidence: 99%
“…64 Typically, mobility is higher within sulphides than oxides, and indeed there are only a handful of oxide materials that report reversible Mg 2+ intercalation. [65][66][67] Experimental results indicate that Mg 2+ ions can be introduced into Y 2 Ti 2 S 2 O 5 via a solid-state reaction route at 300 C, to a stoichiometry of Mg 0.32 Y 2 Ti 2 S 2 O 5 . Mg 2+ ions were found to occupy 12-coordinated sites within the type I cavities.…”
Section: Mg Intercalation and Mobilitymentioning
confidence: 99%
“…The 66 which is structurally-related to the tetragonal tungsten bronzes, and has units similar to type I and II W-R-type cavities. Activation barriers of similar magnitude were reported for selected pathways and Mg-ions we found to occupy distorted square-or rectangular-planar insertion sites.…”
Section: Mg Intercalation and Mobilitymentioning
confidence: 99%
“…The use of CHFS enabled the production of nano-sized crystallites via highly supersaturating conditions and a short reaction time (residence time on the order of a few seconds), 25,26 and the process has previously produced a wide variety of high-performance nanosized electrode materials for Mg batteries, Liion batteries and supercapacitors. 17,[27][28][29][30][31] Experimental section…”
Section: Introductionmentioning
confidence: 99%